Elemental composition of small pelagic fishes in three East African lakes: Implications for nutritional security - Clarke, Shelby B.; Nesbitt, William A.; Efitre, Jackson; Masette, Margaret; Chapman, Lauren J. (Fisheries Research, 2022)
Micronutrient deficiencies and food insecurity constitute major threats to human health across Africa. With decreasing availability of large-bodied fishes (>20 cm), strategies have developed to target small pelagic fish (SPF) species (<20 cm total length) to improve the food availability; yet little is known regarding their nutritional content. Three species of SPFs - Engraulicypris bredoi (muziri), Brycinus nurse (ragoogi) and Rastrineobola argentea (mukene) - were collected from lakes Albert, Victoria, and Nabugabo in Uganda, East Africa. The content of essential elements (Ca, Fe, K, Mg, Na, P, Se, and Zn) and non-essential, potentially toxic elements (Cd and Pb) were measured and compared in fishes across landing sites within lakes Victoria (R. argentea) and Albert (B. nurse, E. bredoi) and between lakes (R. argentea). Rastrineobola argentea was the most nutritious of the fishes examined, although some variation was present in their elemental concentration among landing sites. Overall, all three species contain high levels of essential nutrients and fall within a safe range for non-essential, toxic elements based on current consumption habits. These SPFs can play an important role in addressing nutritional deficiencies in Uganda, and effort should be made to increase the availability, accessibility, and consumption of these under-utilized small fishes.
Keywords: Fisheries; Human health; Lake Victoria; Lake Albert; Nutritional deficiencies